Air pollution and its effect on upper respiratory tract infections: A scoping review from 2010 to 2019 - Mai, Bui Thi; Trang, Nguyen Thi Huyen; Tam, Tran Van; Trang, Nguyen Thu; Trang, Nguyen Thi Ha; Quan, Pham Hong; Phuong, Vu Thu; Van, Hoang Thi Hong; Diep, Nguyen Ngoc; Dat, Le Minh (Tạp chí Nghiên cứu Y học, 2024)
Air pollution is a significant global health concern, linked to numerous severe health outcomes, particularly respiratory infections. However, the effects of air pollution components on upper respiratory tract infections (URTI) remain limited. This study aims to synthesize the impact of air pollution on URTI from 2010 to 2019 to provide a basis for effective public health interventions. A total of 23 studies were included in the analysis, with results showing that pollutants such as PM10, PM2.5, NO2, SO2, and O3 were closely linked to URTI, particularly in children. PM10 and PM10 were identified as having the greatest impact. These findings affirm the need for further research to develop effective pollution control measures, thereby reducing the burden of upper respiratory tract infections.